Nutritional Status and Cognitive Function in the Adolescent’s Rapid Growth Phase between 12-14 Years Old - Ratna Indriawati; Citra Kartika; Tunjung Wibowo (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
Adolescence is a period of transition from childhood to adulthood. One of the transitions is the cognitive aspect of thinking ability. Poor nutritional status can harm children's growth and development. The factors that influence cognitive development are the nutritional status that affects adolescent intellectual development. The relationship between the nutritional status and the cognitive function in the adolescent’s rapid growth phase between 12-14 years old is not clear. This study aims to identify the relationship between the nutritional status and the cognitive function in the adolescent’s rapid growth phase between 12-14 years old. This study used observational analytical design and a cross- sectional approach with an adolescent group population of 12-14 years old. The research subject was a total of 71 people. Primary data included weight and height while secondary data included MMSE-Child and questionnaires. The data were analyzed using the Chi-Square statistical test. Based on the measurement of Body Mass Index (BMI), most research subjects had a normal nutritional status with a total of 32 people (45.10%). Furthermore, 63 people (88.70%) have a normal cognitive function. There was no significant relationship between Nutritional Status and MMSE scores (p=0.454). Likewise there were no significant relationship between gender and MMSE scores (p=0.750), age and MMSE scores (p=0.255). In this study, there was no significant relationship between nutritional status and cognitive function.